2002
DOI: 10.2105/ajph.92.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Highly Active Antiretroviral Treatment on HIV Seroincidence Among Men Who Have Sex With Men: San Francisco

Abstract: Any decrease in per contact risk of HIV transmission due to HAART use appears to have been counterbalanced or overwhelmed by increases in the number of unsafe sexual episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(200 citation statements)
references
References 52 publications
6
191
1
2
Order By: Relevance
“…At this stage, 101 articles were excluded for not meeting inclusion criteria, and the full-text versions of 65 articles were pulled for further screening. Of these, 3 articles met the criteria for inclusion in this review as a primary article (Moatti et al, 2003;Bateganya et al, 2005;Bunnell et al, 2006), and 59 were included as background articles (Mussico et al, 1994;Kelly et al, 1998a;Kelly et al, 1998b;Remien et al, 1998;van der Straten, 1998;DeNoon, 1999;Misovich et al, 1999;Colebunders et al, 2000;Erbelding et al, 2000;Miller et al, 2000;Vanable et al, 2000;van der Straten et al, 2000;Wood et al, 2000;Catz et al, 2001;Dukers et al, 2001;Vlahov et al, 2001;Bouhnik et al, 2002;Chen et al, 2002;Crepaz et al, 2002;Demmer, 2002;DiClemente et al, 2002;Hosseinipour et al, 2002;Katz et al, 2002;Laporte, 2002;Nollen et al, 2002;Ostrow et al, 2002;Gray et al, 2003; International Collaboration on HIV Optimism, 2003;Rietmeijer et al, 2003;Rothenberg et al, 2003;Stephenson et al, 2003;Xiridou et al, 2003;Boily et al, 2004;Crepaz et al, 2004;Fang et al, 2004;…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, 101 articles were excluded for not meeting inclusion criteria, and the full-text versions of 65 articles were pulled for further screening. Of these, 3 articles met the criteria for inclusion in this review as a primary article (Moatti et al, 2003;Bateganya et al, 2005;Bunnell et al, 2006), and 59 were included as background articles (Mussico et al, 1994;Kelly et al, 1998a;Kelly et al, 1998b;Remien et al, 1998;van der Straten, 1998;DeNoon, 1999;Misovich et al, 1999;Colebunders et al, 2000;Erbelding et al, 2000;Miller et al, 2000;Vanable et al, 2000;van der Straten et al, 2000;Wood et al, 2000;Catz et al, 2001;Dukers et al, 2001;Vlahov et al, 2001;Bouhnik et al, 2002;Chen et al, 2002;Crepaz et al, 2002;Demmer, 2002;DiClemente et al, 2002;Hosseinipour et al, 2002;Katz et al, 2002;Laporte, 2002;Nollen et al, 2002;Ostrow et al, 2002;Gray et al, 2003; International Collaboration on HIV Optimism, 2003;Rietmeijer et al, 2003;Rothenberg et al, 2003;Stephenson et al, 2003;Xiridou et al, 2003;Boily et al, 2004;Crepaz et al, 2004;Fang et al, 2004;…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Evidence points to corresponding high rates of drug use, suggesting that drug use may be contributing to higher levels of sexual risk behavior. 3 The general relationship between noninjection drug use and HIV risk behavior has been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Study findings did not document a correlation between UAS or group sex. Earlier studies have reported mixed findings and documented that medication adherence [8] and availability [10][11][12][13] are related to lower and higher UAS, respectively. Clearly larger sample sizes might be needed to provide more precise estimates and clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these findings did not examine interaction effects to understand if the association is moderated by ethnicity and/or sexual orientation and it remains unclear whether this relationship was significant for YBMSM. In contrast, several studies that compare risk behavior before and after 1996 have reported that the availability of highly active antiretroviral therapy (HAART) was associated with increased risky sexual behaviors (e.g., unprotected anal sex; having multiple sexual partners; unprotected anal sex with two or more partners of unknown HIV serostatus) among MSM populations [10][11][12][13] . Additionally, given the propensity for higher levels of psychological distress associated with having an HIV diagnosis [14,15] , it is unclear whether medication adherence might be related to less psychological distress.…”
Section: Introductionmentioning
confidence: 99%